Optimalisasi Edupreneurship di Pondok Pesantren untuk Membentuk Santripreneur Berdaya Saing dan Mandiri di Era Milenial - Arwin, Arwin; Sugiharto, Vebri; Nisa, Ardina Khoirun (Sekolah Tinggi Agam Islam Sumatera Medan, 2023)
The millennial era requires the younger generation to have skills such as self-confidence, sociability, openness to change, and creativity. Generations that do not have these skills will gradually be eroded and ostracized. Islamic boarding schools as Islamic educational institutions are expected to be able to produce graduates who are experts in the field of religion as well as skilled and creative in entrepreneurship. In this regard, this study aims to analyze the optimization of edupreneurship carried out by Islamic boarding schools in producing competitive and independent santripreneurs. This research was conducted at the Padangsidimpuan Islamic boarding school. The research method used is qualitative based on descriptive studies. The data sources in this study were the heads of Islamic boarding schools, extracurricular teachers, and students. Data collection uses observation and interviews. The results showed that optimization was carried out in several ways, namely integrated edupreneurship in all subjects, integrated in the form of extracurricular activities, self-development programs, integrated into teaching materials, through Islamic boarding school culture, integration through local content.